A spatial and demographic analysis of cycling safety perceptions: A case study in Eau Claire, Wisconsin, USA - Matthew Haffner; Nathan Walker; Savanna Grunzke; Matthew St. Ores (REGION)
Bike-friendly cities offer scores of benefits to both individuals and society, but a lack of safety is a major barrier to ridership. Significant research has been devoted to studying demographic drivers of ridership and what makes individuals feel unsafe on a bicycle, but there is lack of research utilizing quantitative approaches on spatial perceptions of safety, particularly with respect to gender. This paper seeks to close that gap using a crowd sourcing approach to spatial data collection, statistical comparisons of cycling behavior by gender, and spatial analyses of mapped points. The authors find parity between women and men in terms of number of trips taken per week but find significant differences in the spatial extent of mapped responses. This paper adds to academic discussions on cycling safety and sheds light on specific locations that could benefit from infrastructure improvements.